2007
DOI: 10.1128/aem.02765-06
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Degradation of N,N -Diethyl- m -Toluamide (DEET): Cloning and Heterologous Expression of DEET Hydrolase

Abstract: Pseudomonas putida DTB grew aerobically with N,N-diethyl-m-toluamide (DEET) as a sole carbon source, initially breaking it down into 3-methylbenzoate and diethylamine. The former was further metabolized via 3-methylcatechol and meta ring cleavage. A gene from DTB, dthA, was heterologously expressed and shown to encode the ability to hydrolyze DEET into 3-methylbenzoate and diethylamine.N, N-diethyl-m-toluamide (DEET) is the active ingredient in most topical insect repellent products. Approximately 30% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 18 publications
2
23
3
1
Order By: Relevance
“…Previously we suggested that Ser166, Asp292 and His320 constitute the catalytic triad, on the basis of sequence alignment data [7]. In addition, we observed that serine protease inhibitors were able to inhibit the activity of DthA, further supporting the role of a serine as the enzymatic nucleophile.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Previously we suggested that Ser166, Asp292 and His320 constitute the catalytic triad, on the basis of sequence alignment data [7]. In addition, we observed that serine protease inhibitors were able to inhibit the activity of DthA, further supporting the role of a serine as the enzymatic nucleophile.…”
Section: Resultssupporting
confidence: 70%
“…Previously, we reported homology between DthA and CocE (24% sequence identity with blast ) [7]. Therefore, we wanted to know whether DthA was also active on cocaine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown a close relationship between stable NH þ 4 N removal and the removal of many TrOCs including atenolol (Helbling et al, 2012), ibuprofen and naproxen (FernandezFontaina et al, 2014), and gemfibrozil (Maeng et al, 2013). Also DEET was shown to be metabolized only in the presence of nitrogen (Rivera-Cancel et al, 2007). Of particular relevance to the observed drop in TrOC removal due to rise in influent NH þ 4 N concentration is the study of De Gusseme et al (2009) who showed that nitrifying cultures may preferentially oxidize ammonia rather than the synthetic estrogen 17a-ethinyl estradiol under elevated NH þ 4 N concentration.…”
Section: Correlation Between Tn and Troc Removalmentioning
confidence: 88%
“…Metabolites produced after incubation of the fungi with DEET (N,N‐diethyl ‐m‐ toluamide), included N‐ethyl ‐m‐ toluamide, N,N‐diethyl ‐m‐ toluamide‐N‐oxide, and N‐ethyl ‐m‐ toluamide‐N‐oxide. Using another test system, Rivera‐Cancel et al (2007) isolated a Pseudomonas putida DTB species from activated sludge collected at a municipal WWTP. The bacteria were incubated over a 98‐h period in minimal salts medium amended with 2.6 mM DEET.…”
Section: Resultsmentioning
confidence: 99%